Construction and Application of a Carbon Emission Model for China’s Coal Production Enterprises and Result Analysis - Li, Yang; Jin, Xiangyang; Wang, Guoliang; Ren, Yuqi; Tan, Huiqi; Li, Na (Frontiers in Energy Research, 2022)
To achieve the national goal of “peak carbon emissions and carbon neutrality,” a specific action plan is needed. Therefore, it is particularly important to scientifically calculate the total carbon emissions of enterprises in various industries. According to the related enterprises’ characteristics, this study adopts different-source methods to construct the carbon emission calculation model. Carbon dioxide emissions are calculated based on the gas grade, and the results are as follows: 1) Carbon emissions of enterprises are significantly different with various gas grades; 2) gas dissipation accounts for more than 80% of carbon emissions of relevant enterprises, so the gas content in the coal seam increases the effect of carbon emissions; and 3) with the increase in mining depth, carbon emissions are increasing. This innovation of study is, first, comprehensively analyzing the carbon emission sources of relevant enterprises from six aspects, including fuel combustion, torch burning, CH4 and CO2 dissipation, net purchased electricity and heat implication, coal gangue storage and utilization, and coal transportation. Moreover, the source–sink relationship method is proposed when the CH4 and CO2 dissipation is calculated, which avoids human errors such as inaccurate measurement of the actual statistical method and the difficulty of obtaining calculation parameters, thus more accurately calculating the total carbon emissions. The source–sink relationship method can be applied in open coal pits to solve the carbon emission calculation. Implementing green and low-carbon development and achieving the goal of peak carbon emissions and carbon neutrality is significant.